COMMENTARY: A trauma shake-up: Are NZ graduates being prepared for the real world? - Lyn Barnes (Asia Pacific Network, 2013)
Young journalists today are highly likely to cover traumatic incidents early in their careers, with many confronting trauma day to day. This pressure is exacerbated in the current economic climate and fast-paced changing world of journalism. New Zealand graduates are no exception. Few are prepared by their journalism schools to deal with trauma. Should they be taught these skills during their training or should they wait until they are in the workplace? Research has recommended the former for at least two decades. Perhaps it is time New Zealand caught up with many American and Australian journalism schools and introduced changes to the journalism curricula to ensure graduates are equipped with skills to recognise signs of stress in themselves as well as victims. The workplace can support this training with recognition and support, which has been shown to improve productivity and resilience.